A novel approach to N,N'-dimethyl and N,N'-ethylene bridged dibenzodithiadiazafulvalane - Časar, Zdenko (Acta chimica slovenica, 2002)
A novel approach to electron rich olefins, such as dibenzodithiadiazafulvalenes (DTDAFs) is reported. These compounds have been prepared by alkalination of the benzothiazole-2-thione ring. The first crystal structure of the N,N'-dimethyl dibenzoDTDAF dicationis also reported.
Keywords: benzotiazol; dikation; ditiadiazafulvalen; organska kemija; sinteza